2010
DOI: 10.1007/s12665-009-0417-6
|View full text |Cite
|
Sign up to set email alerts
|

Environmental status of the metropolitan river (Kifissos) of Athens, Greece

Abstract: Surficial and sub-surficial sediments obtained from the lower course of the Kifissos River, which drains the Athens Basin, have been analyzed for heavy metals and aliphatic and polycyclic hydrocarbons. Oddly, the calculated enrichment factors for the identified heavy metals, with the baseline taken from a pristine area in the adjacent Saronikos Gulf, are very low excluding only those related to Cu and Zn. In contrast, the enrichment factors for the measured hydrocarbons are particularly high. However, physicoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…High concentrations of this particular element are probably linked to biogeochemical processes within the streamwater-sediment interface. Data of heavy metal concentrations are also comparable to values reported by Panagiotopoulos et al (2010) for surficial and sub-surficial sediments obtained from the lower course of the Kifissos River. In their study, the calculated enrichment factors for the identified heavy metals, with the baseline taken from a pristine area in the adjacent Saronikos Gulf, were very low.…”
Section: Heavy Metals In Water and Stream Sedimentsupporting
confidence: 85%
“…High concentrations of this particular element are probably linked to biogeochemical processes within the streamwater-sediment interface. Data of heavy metal concentrations are also comparable to values reported by Panagiotopoulos et al (2010) for surficial and sub-surficial sediments obtained from the lower course of the Kifissos River. In their study, the calculated enrichment factors for the identified heavy metals, with the baseline taken from a pristine area in the adjacent Saronikos Gulf, were very low.…”
Section: Heavy Metals In Water and Stream Sedimentsupporting
confidence: 85%
“…The extract was saponified with methanolic KOH, and the non-saponified material was extracted with n-hexane, then cleaned up and fractionated by silica column chromatography. Two fractions were obtained, the first containing aliphatic hydrocarbons and the second the polyaromatic compounds (Zenetos et al 2004;Panagiotopoulos et al 2010).…”
Section: Sampling and Chemical Analysismentioning
confidence: 99%
“…The main highway runs along the river basin, and the last 10 km of the river corridor are channeled under the highway. All these activities led to the chemical pollution of the river water and sediments [34,35]. The Pinios Thessaly River basin is located in central Greece, one of the most intensely cultivated agricultural areas, and flows out into the Aegean Sea (Figure 1).…”
Section: Introductionmentioning
confidence: 99%